Associations between Computer Game Addiction and Attention Deficit and Hyperactivity Disorder - An Emprical Study - Başgül, Şaziye Senem; Bekar, Bengi; Luş, Melek Gözde (Addicta: The Turkish Journal on Addictions, 2020)
The aim of this study is to compare the video game addiction levels and habit of playing computer games between children with attention deficit hyperactivity disorder (ADHD) and healthy children. The study group consisted of 100 children aged between 10 and 13 years who were diagnosed with ADHD and who applied to the psychiatry clinic in the province of Istanbul. The control group consisted of 100 healthy children between the ages of 10 and 13 years with no psychiatric diagnoses and were matched with the study group in terms of sociodemographic characteristics. The Personal Information Questionnaire and the Computer Game Addiction Scale for Children (CGASC) were applied to the participants. Children with ADHD had significantly higher levels of video game addiction than healthy children. Video game addiction levels were found to be higher in children who play action, shooter, and racing games than those who did not play them. Furthermore, online gaming has been found to have a significant effect on the level of video game addiction.